APLIKASI MAT DALAM PENGENDALIAN LALAT BUAH BACTROCERA SP. (DIPTERA : TEPHRITIDAE) PADA TANAMAN CABE - Lengkong, Maxi; Rante, Caroulus S.; Meray, Merlyn (EUGENIA, 2011)
ABSTRACT   Research was aiming to determine the effectiveness of the attractant methyl eugenol + traps modification in the catch of species of fruit flies in the chilli plants at any given time and to identify the types of fruit flies trapped with methyl eugenol + traps modification on chilli crop acreage. The field research was conducted in the area of chilli crop in three places namely District Pineleng, Tompaso / Langowan and Modoinding. Observation number and type of fruit flies was performed at intervals of 2 weeks of observation for 3 months. The result showed that the number of fruit fly caught or trapped dead at 30 traps set in chilli crop acreage was 1278. The highest trapped was 164 whereas the lowest trapped was 89. The number of male fruit flies trapped was high implying that reduction of male fruit fly population in the field. There were five types of fruit flies identified from area of Pineleng, Tompaso and Modoinding namely Bactrocera umbrosa Fabricus, Bactrocera dorsalis (Hendel), Bactrocera philippinensis, Bactrocera carambolae, and Bactrocera sp. The five types were attracted to methyl eugenol. Key words : MAT (male annihilation technique), Bactrocera umbrosa Fabricus, B. dorsalis (Hendel), B. philippinensis, B. carambolae